Hubungan Tingkat Stres dengan Kualitas Tidur pada Ibu Preeklamsi di Wilayah Kerja Puskesmas Tempurejo-Jember - Dyan Ayu Pusparini; Dini Kurniawati; Enggal Hadi Kurniyawan (UPT Percetakan dan Penerbitan Universitas Jember, 2021)
Preeclampsia is some of the symptoms that occur in pregnancy, childbirth, and puerperal women, which are characterized by hypertension, edema, and increased proteinuria. Preeclampsia usually occurs when pregnancy enters the age of 20 weeks to 48 hours after the birth process. In that condition, there are undesirable complications during pregnancy that can make mothers more vulnerable to psychological disorders, one of which is stress. Stress experienced during pregnancy can affect the health of the baby and can also improve poor sleep quality. This study aims to analyze the relationship of stress levels with the quality of preeclampsia sleep in the Tempurejo Community Health Center in Jember. This research was conducted on 31 preeclampsia mothers using a correlational research design with a cross-sectional approach and total sampling techniques. Data collection using questionnaires stress and sleep quality. The results showed 19 (61.3)% of respondents experienced mild stress, and 26 (83.9)% experienced poor sleep quality. The results of data analysis using the spearmen statistical test obtained p-value 0.001 and r = 0.894, which means there is a relationship between stress levels and sleep quality or ha is accepted. R-value = 0.396 means that the correlation between stress levels and sleep quality in preeclampsia has a positive correlation with weak correlation strength. Nursing implications for further research can intervene in interventions that can reduce stress levels with the quality of sleep in preeclampsia mothers to reduce the factors of preeclampsia.